Factors Affecting Brand Loyalty of Facial Cream in Shanghai Cosmetic Market - Zhang, Ying (2009)
The purpose of this research is to investigate main factors that influencing brand loyalty in Shanghai cosmetic market. Furthermore, it identifies current brand loyalty level in Shanghai cosmetic market. The first part of this paper introduces the background of China cosmetic market, problem definition, research objectives and significance of this study. The second part is about literature review. Previous research mentions demographic of consumers (gender, age, income and education) and other four factors (brand name, product quality, and store environment and service quality) may affect brand loyalty in cosmetic industry. Above eight factors are adopted in this study. The third part of this paper is research methodology that include source of data, questionnaire and data analytic methods. Questionnaires are distributed and self-administrated to 200 customers who visit in shopping mall. The chapter four is relevant to data analysis. The research result shows current brand loyalty level in Shanghai cosmetic market is relatively low. Income and education level positively affect brand loyalty in Shanghai cosmetic market. The findings indicate there is a positive relationship between (brand name, product quality and service quality) and brand loyalty in cosmetic market. Among these factors, product quality is the most important factor affecting brand loyalty. The last part of this paper provides conclusions and reasonable recommendation. Hence, it encourages cosmetic companies to endeavor in improve cosmetic quality. Furthermore, cosmetic companies ‘promote’ their brand name and carry out appropriate human resource policies to improve service quality.